Les terres cuites grecques : Pour qui ? Pourquoi ? Comment ? - Christophe Hugot; Stéphanie Huysecom-Haxhi; Arthur Muller (Les Carnets de l’ACoSt)
The research carried out on coroplastics at the University of Lille over the last thirty years resulted in an exhibition held in March 2016. Three sections answering the questions: For whom? Why? How? presented the two main successive issues addressed in Lille: the study of a craft and its mass production processes ; archeology of religion, with the definition of the function of the figurines in the sanctuary and the tomb.